Safeguard and Mitigation of Hazard and Operability during Simultaneous Production and Drilling at Oil and Gas Platform - Shafie, Nur Liyana; Mohammad, Roslina (Progress in Energy and Environment, 2023)
Safety in the SIPROD platform design primarily relies on applying various codes of practice or design based on the broad experience and knowledge of professional experts and specialists in the industry. One technique used to study the potential hazards and consequences is the HAZOP study which is defined as the application of formal systematic critical examination to the process and engineering intentions of new or modified SIPROD facilities to assess the hazard potential of individual items of equipment and the consequential effect on the SIPROD facility as a whole. The application is backed up by local SIPROD platform managers, engineers, and operators with direct experience in the relevant plant operation. The HAZOP session describes the SIPROD process and systematically questions each design part by breaking it into pieces or nodes. Each node is assessed using guide words and deviations to discover how these deviations from the original design intent can occur and the resultant hazards and maintenance problems. There may be a deviation in identifying controls that need further investigation. This paper discusses the adequacy of the safeguards concerning safety and operations at the SIPROD platform, evaluates additional safeguards required for the system under study to address and minimize the consequence of deviation, and recommends ways to mitigate the consequences of deviations and return to normal and safe operations.